Clinical characteristics and prognostic value of renal immune complex deposition in patients with light chain amyloidosis - Yan, Jipeng; Wang, Di; Zhao, Jin; Zhou, Meilan; Huang, Boyong; Xing, Yan; Guo, Wei-Feng; Sun, Shiren (Frontiers in Oncology, 2022)
Although patients with light chain amyloidosis (AL) may present with co-deposition of amyloid and immune complexes (ICs) in renal biopsies, data on clinical characteristics and prognostic value of renal IC deposition are limited. A total of 73 patients with AL amyloidosis who were newly diagnosed by renal biopsy in Xijing Hospital (Xi’an, China) were divided into two groups (IC and non-IC groups). As a result, renal IC deposition was found in 26% of patients. Patients with IC deposition were associated with more urinary protein excretion and lower serum albumin. Notably, patients in the non-IC group achieved higher hematological overall response rate (81.5% vs. 47.4%, p = 0.007) and ≥VGPR rate (75.9% vs. 39.8%, p = 0.004) compared with those in IC group. Renal response rate was also higher in the non-IC group (63% vs. 31.6%, p = 0.031). With the median follow-up time of 19 months, a significantly worse overall survival was observed in patients with the IC group as compared with those without renal IC deposition in the Kaplan–Meier analysis (p = 0.036). Further multivariate analysis demonstrated that renal immune complex deposition was associated with worse overall survival in patients with AL amyloidosis (HR 5.927, 95% CI 2.148–16.356, p = 0.001).